PENGEMBANGAN MEDIA KOMIK BERBASIS CANVA PADA PEMBELAJARAN PPKn MATERI HAK DAN KEWAJIBAN KELAS IV SEKOLAH DASAR - Saptiana, Reni; Fauziah, Muhardila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to: 1) Develop Canva-based comic media for instructing Civics on the topic of rights and obligations. 2) Determine the feasibility of Canva-based comic media according to material and media expert validators. 3) Determine the practicality of Canva-based comic media based on teacher and student responses. 4) Determine the effectiveness of using Canva-based comic media based on student pretest and posttest results. This study used the Research and Development (R&D) method with a 4-D development model. The subjects of this research were 52 fourth-grade students from Ngrukeman Elementary School and Kadipiro 2 Elementary School. Data were collected through observation, tests, questionnaires, and documentation. Data analysis involved assessing the feasibility, practicality, effectiveness of the developed media. The results of the feasibility test by material and media experts were 96% and 87,67%, respectively, indicating that the Canva-based comic media is highly feasible to use. The practicality test results showed the teacher responses 82,17% and student responses 93,92%, which showed that Canva-based comic media was in the very practical category. Additionally, the effectiveness test results showed an average pretest score of 64,04 and a posttest score of 84,90. The pretest results obtained an average value of 64.04, while the posttest results obtained an average value of 84.90. The paired sample t-test results showed a sig. (2 tailed) < 0.05, which is 0.00, indicating a significant difference between learning outcomes in the pretest and posttest data. Therefore, it can be concluded that this Canva-based comic media is effective for use in learning civics lessons on the topic of rights and obligations.